1983
DOI: 10.1002/ijch.198300060
|View full text |Cite
|
Sign up to set email alerts
|

Cosensitized Electron‐Transfer Photooxygenation of Epoxides. A New Synthesis of Ozonides

Abstract: 9,10‐Dicyanoanthracene (DCA) and biphenyl (BP) cosensitize the electron‐transfer photooxygenation of epoxides in oxygen‐saturated acetonitrile to form ozonides. These epoxides do not measurably quench the fluorescence of DCA and are, therefore, relatively unreactive under standard photooxygenation conditions with only DCA as sensitizer. However, a dramatic increase in the rate of reaction is observed upon the addition of BP as a non‐light‐absorbing cosensitizer. An investigation of the stereochemistry of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…One of the most prolific areas of study for this type of cocatalysis is the photooxygenation of cycloalkanes and small saturated heterocycles . In the 1980s, the Schaap group discovered that biphenyl provided a dramatic rate increase to the DCA-catalyzed oxidation of cyclopropanes, epoxides, and aziridines . For example, the photooxygenation of epoxide 19 to 20 is a slow reaction upon photocatalysis using DCA alone (Scheme ).…”
Section: Photoinduced Electron Transfersupporting
confidence: 55%
“…One of the most prolific areas of study for this type of cocatalysis is the photooxygenation of cycloalkanes and small saturated heterocycles . In the 1980s, the Schaap group discovered that biphenyl provided a dramatic rate increase to the DCA-catalyzed oxidation of cyclopropanes, epoxides, and aziridines . For example, the photooxygenation of epoxide 19 to 20 is a slow reaction upon photocatalysis using DCA alone (Scheme ).…”
Section: Photoinduced Electron Transfersupporting
confidence: 55%
“…First of all, the 18 O-tracer experiments were examined by using the 18 O-labeled ozonide 18 O-1a ( 18 O, 77%), 12 in which the ethereal oxygen was labeled by 18 O atom (eq 2). The labeled ozonide 18 O-1a was prepared by an electron transfer photooxygenation 13 of the 18 O-labeled epoxide 18 O-7 ( 18 O-77%), which was prepared by the epoxidation of 1,2-diphenylcyclopentene by using 18 O-labeled m-CPBA as depicted in eq 2 (see Experimental Section). The 18 O content (%) of the epoxide 18 O-7 was calculated from the relative mass peak intensities of 236 (M + ) and 238 (M + 2 + ), comparing with those of the unlabeled epoxide 7 (see Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The reduction showed that the 18 O-labeled diketone 18 O-11a ( 18 O, 39%; mass spectroscopic analysis) was obtained in a similar yield to the unlabeled case. To identify which oxygen in the diketone 11a contains 18 O atom, the highly resolved 13 C NMR (150 MHz) analysis was performed (Figure 2). In the carbonyl carbon region, only three signals, δ 197.03, 197.07, 198.33, which correspond to one 18 Olabeled carbonyl carbon and two unlabeled carbonyl carbons, were detected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some years ago, Schaap and co-workers developed a method by which compounds that do not quench the fluorescence of the singlet excited DCA sensitizer may nevertheless be rapidly oxidized [102,108,109,[160][161][162]. For example, epoxides 69a-d, unreactive under standard DCA-sensitized conditions [107,163], can be readily converted into the corresponding ozonides 70a-c, in high yields, by use of a non-light-absorbing aromatic hydrocarbon, i.…”
Section: Cosensitized Cyanoaromatic-sensized Photooxygenation Of Orgamentioning
confidence: 99%